Principles of Normal Childbirth Care in Obstetrics and Gynecology Literature - Dwi Andina Farzani (Indonesian Journal Publisher, 2026)
This study aims to explore and synthesize the Principles of Normal Delivery Care (Asuhan Persalinan Normal—APN) within the context of obstetric and gynecological literature to identify key concepts, clinical standards, and their practical implications for maternal and neonatal health. Using a qualitative descriptive approach through a library-based study, data were collected from peer-reviewed articles, clinical guidelines, and national midwifery standards published between 2015 and 2025. Data were analyzed inductively through thematic identification, reduction, categorization, and interpretation to generate a comprehensive understanding of APN principles. The findings reveal that normal delivery care emphasizes the physiological nature of childbirth, prioritizing safety, minimal intervention, and positive maternal experience. Recommended practices include the use of partographs, freedom of movement, non-pharmacological pain management, continuous support, delayed cord clamping, and immediate skin-to-skin contact. Conversely, routine interventions such as enemas, pubic shaving, and fundal pressure are discouraged. Psychosocial aspects—such as emotional support, hypnobirthing, and calm birthing environments—are shown to significantly improve labor outcomes. However, discrepancies persist in the consistency of APN implementation, influenced by systemic, behavioral, and institutional factors. This study concludes that effective APN practice requires not only clinical competence but also cultural sensitivity, organizational reform, and woman-centered care frameworks. The results contribute to strengthening obstetric practice standards and guiding future research toward more holistic, evidence-based maternity care.